Strain-specific morphological response of the dominant calcifying phytoplankton species Emiliania huxleyi to salinity change. - Christina Gebühr; Rosie M Sheward; Jens O Herrle; Jörg Bollmann (PLoS ONE, 2021)
The future physiology of marine phytoplankton will be impacted by a range of changes in global ocean conditions, including salinity regimes that vary spatially and on a range of short- to geological timescales. Coccolithophores have global ecological and biogeochemical significance as the most important calcifying marine phytoplankton group. Previous research has shown that the morphology of their exoskeletal calcified plates (coccoliths) responds to changing salinity in the most abundant coccolithophore species, Emiliania huxleyi. However, the extent to which these responses may be strain-specific is not well established. Here we investigated the growth response of six strains of E. huxleyi under low (ca. 25) and high (ca. 45) salinity batch culture conditions and found substantial variability in the magnitude and direction of response to salinity change across strains. Growth rates declined under low and high salinity conditions in four of the six strains but increased under both low and high salinity in strain RCC1232 and were higher under low salinity and lower under high salinity in strain PLYB11. When detailed changes in coccolith and coccosphere size were quantified in two of these strains that were isolated from contrasting salinity regimes (coastal Norwegian low salinity of ca. 30 and Mediterranean high salinity of ca. 37), the Norwegian strain showed an average 26% larger mean coccolith size at high salinities compared to low salinities. In contrast, coccolith size in the Mediterranean strain showed a smaller size trend (11% increase) but severely impeded coccolith formation in the low salinity treatment. Coccosphere size similarly increased with salinity in the Norwegian strain but this trend was not observed in the Mediterranean strain. Coccolith size changes with salinity compiled for other strains also show variability, strongly suggesting that the effect of salinity change on coccolithophore morphology is likely to be strain specific. We propose that physiological adaptation to local conditions, in particular strategies for plasticity under stress, has an important role in determining ecotype responses to salinity.